2012
DOI: 10.1186/2191-1991-2-15
|View full text |Cite
|
Sign up to set email alerts
|

Assessing DRG cost accounting with respect to resource allocation and tariff calculation: the case of Germany

Abstract: The purpose of this paper is to analyze the German diagnosis related groups (G-DRG) cost accounting scheme by assessing its resource allocation at hospital level and its tariff calculation at national level. First, the paper reviews and assesses the three steps in the G-DRG resource allocation scheme at hospital level: (1) the groundwork; (2) cost-center accounting; and (3) patient-level costing. Second, the paper reviews and assesses the three steps in G-DRG national tariff calculation: (1) plausibility check… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 27 publications
0
59
0
5
Order By: Relevance
“…The cost homogeneity coefficient (CH) for a DRG was calculated according to the formula CH = 1/(1 + σ/μ), where σ = SD and μ = arithmetic mean [9]. …”
Section: Methodsmentioning
confidence: 99%
“…The cost homogeneity coefficient (CH) for a DRG was calculated according to the formula CH = 1/(1 + σ/μ), where σ = SD and μ = arithmetic mean [9]. …”
Section: Methodsmentioning
confidence: 99%
“…Wiegard et al [22] underline that health-related quality of live in relation to breast cancer treatment is determined essentially by a patient's psychological state. Not implemented in the previous definition of DRG-based reimbursement per case, an increasing amount of non-DRG-relevant costs arise for instance from ambulatory care, research and teaching, psychological, psychiatric and psycho-oncological care, as well as amortizations [23]. In principle, the need for a service portfolio of complementary and alternative medicine (CAM) is underscored by the study of Matsuno [24] on breast cancer survivors who reported that they perceived CAM therapies as helpful.…”
Section: Business Competition - the Driving Force For Improvement? Inmentioning
confidence: 99%
“…In most cases, these fall below the average daily reimbursement for the first 14 days. Accordingly, for TB patients under statutory health insurance, hospitals do well to keep the total number of patients treated high, but to keep the duration of their hospital stays as short as possible [5,6].…”
Section: Introductionmentioning
confidence: 99%